Penerapan Model Pembelajaran Project Based Learning (PJBL) Dan Media Audio Visual Untuk Meningkatkan Kemampuan Memproduksi Teks Negosiasi Pada Siswa Kelas X AKL 3 SMK Negeri 6 Medan Tahun Ajaran 2022/2023 - Juni Warohmah; Mutia Febriyana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In the process of learning to write, students have the potential, interests and needs to be developed by the teacher. Therefore, the teacher has an important role in the language learning process, especially in the aspect of writing skills. The facts that occur in the field from the results of the author's observations in class X AKL 3 SMK N 6 Medan, the Indonesian language learning process is still not good enough compared to the mandatory learning process contained in the 2013 curriculum. And student learning outcomes in Indonesian, especially in the basic competence of writing negotiating texts, are still low. Therefore, to improve students' ability to write negotiating texts, learning models and media are needed so that students are able to write negotiating texts easily and pleasantly. The models and media used to overcome this are the use of project-based learning models and audio-visual media. With the use of this model and media it is expected that students will find it easy to write negotiating texts, because with these models and media students compose a negotiating text based on their direct experience. The background of the problems above is to implement the use of project based learning learning models and audio-visual media as an effort to improve students' ability to write negotiating texts in class X AKL 3 SMK N 6 Medan. Based on the results of research conducted in cycle I and cycle II in learning to write negotiating text using project based learning media and audio visual media, it was found that there was an increase in write negotiating text. This can be seen from the average value in the first cycle which was 64.78 and increased in the second cycle which was 80.03.